Nanoemulsion of Gomortega Keule Essential Oil: Characterization, Chemical Composition, and Anti-Yeast Activity Against Candida Spp. - Santander-Meyer, R (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Background/Objectives: Candidiasis, an opportunistic fungal infection caused by Candida species, is a major health problem, particularly in immunocompromised individuals. Increasing resistance of yeasts such as Candida spp. to pharmacological antifungal agents makes it necessary to explore alternative treatments. The aim of this study was to evaluate the antifungal potential of Gomortega keule essential oil (GKEO) against Candida spp. by assessing growth and development at 24 and 48 h. Encapsulation and characterization of a stable nanoemulsion were carried out to enhance efficacy. Methods: The anti-yeast activity of both free GKEO and the nanoemulsion against Candida albicans, C. glabrata, and C. guilliermondii was evaluated using a microdilution method to determine the minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) at 24 and 48 h. Results: GC-MS/MS analysis identified forty-one components in GKEO, the main ones being eucalyptol (21.41%), 4-terpineol (19.62%), and α-terpinyl acetate (13.89%). Antifungal assays revealed that both free and nanoemulsion-formulated GKEO inhibited the growth of all tested Candida strains. At 48 h, the nanoformulated GKEO achieved a MIC value of 32 µg/mL and an MFC of 64 µg/mL for C. albicans and C. glabrata and showed higher antifungal activity compared to the free oil, in particular against C. albicans, exhibiting a four-fold lower MFC value. The activity of the nanoformulation was comparable to or better than fluconazole against C. glabrata and C. guilliermondii. Conclusions: The GKEO nanoemulsion potentiated anti-yeast activity against Candida spp. The formulation improved the efficacy of GKEO, suggesting its potential as an alternative or adjunctive treatment for candidiasis. © 2025 by the authors.